2020
DOI: 10.1128/aac.00773-20
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Monocyte Activation and Function during Direct Antiviral Agent Treatment in Patients Coinfected with HIV and Hepatitis C Virus

Abstract: BACKGROUND: The activation phenotype and functional changes in monocyte subsets during HCV elimination in HIV/HCV-coinfected patients were evaluated. METHODS: 22 HIV/HCV-coinfected patients on suppressive combination antiretroviral treatment (cART) achieving HCV elimination after direct-acting antivirals (DAAs) therapy and 10 HIV-monoinfected patients were included. Activation phenotype (10 markers) and polyfunctionality (intracellular IL1α, IL1β, IL6, IL8, TNFα and IL10 production) in three monocyte subsets (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…Secondly, the results of our longitudinal study revealed that HIV-DNA content did not significantly change after HCV eradication, what reinforces the conclusion of our cross-sectional study. The results of our longitudinal study are also in agreement with most previous studies analyzing the evolution of HIV-DNA content after HCV eradication with anti-HCV therapies based on DAAs 7 , 8 , 10 , 11 . In contrast, one study found a significant decrease of HIV-DNA level in HIV/HCV-coinfected patients after HCV eradication 9 .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Secondly, the results of our longitudinal study revealed that HIV-DNA content did not significantly change after HCV eradication, what reinforces the conclusion of our cross-sectional study. The results of our longitudinal study are also in agreement with most previous studies analyzing the evolution of HIV-DNA content after HCV eradication with anti-HCV therapies based on DAAs 7 , 8 , 10 , 11 . In contrast, one study found a significant decrease of HIV-DNA level in HIV/HCV-coinfected patients after HCV eradication 9 .…”
Section: Discussionsupporting
confidence: 92%
“…This discrepancy could be found in the different cohorts of patients included; the different levels of inflammation and liver fibrosis in the studied patients; the different cell populations used to assess the HIV reservoir; and the different methodologies used to measure the HIV reservoir. Interestingly, our current results (using a very homogeneous cohort of HIV/HCV-coinfected and HIV monoinfected patients with paired parameters and with strict selection criteria; in addition, the use of a highly precise and reproducible methodology to measure the HIV reservoir, as well as the use of a highly purified population of CD4 + T cell) are in agreement with previous 5 and more recent 11 cross-sectional studies in different cohorts of HIV/HCV-coinfected and HIV-monoinfected patients under cART 5 , 11 . Thus, the results of our current cross-sectional study demonstrate that presence of HCV coinfection do not significantly impact on the HIV reservoir size in HIV patients with successful cART.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations